Pattern of Fingerprints and Its Association with Gender among Medical Students of Peshawar Medical College: Fingerprint patterns and gender association - Iqbal, Farzand; Alam, Naveed; Yasmin, Rubina Salma; Khattak, M.Asghar; Farid, Noreen; Aziz, Ijaz (Pakistan Journal of Health Sciences, 2024)
Dermatoglyphics is the scientific discipline that studies the patterns and characteristics of fingerprints. When it comes to criminal justice and medical law, fingerprints are crucial. The analysis and comparison of unknown prints found at a crime scene with known prints of witnesses, victims, and possible perpetrators can greatly aid investigators and analysts in their pursuit of justice. Objectives: To identify fingerprint patterns and determine its association with gender among medical students of Peshawar. Methods: This cross-sectional descriptive study was conducted on students of Peshawar Medical College, Peshawar from 1st December 2021 to 1st June 2022. After a multi-stage proportional sampling process, a total of 300 students were included in the study, with 120 females and 180 males. After obtaining written agreement and adhering to stringent inclusion and exclusion criteria, students’ fingerprints were placed on white paper using a stamp pad. The paper already bore the students’ names, ages, sexes, and professional years. Statistical analysis was conducted using SPSS v.25, with descriptive and inferential statistics applied as necessary. Results: The most common fingerprint pattern was the loop pattern, followed by the whorl pattern at 30.33 percent. The average age of the participants in the study was 21.54 ± 2.33 years, with a male-to-female ratio of 1.5:1. All of the fingerprint patterns showed no significant association with gender. Conclusions: The study found that Loop fingerprints were more common than other fingerprints. Also, there is no statistically significant association between gender and fingerprints.